2010
DOI: 10.1111/j.1461-9563.2009.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shade on the spatial distribution of Sahlbergella singularis in traditional cocoa agroforests

Abstract: 1 Shade management is commonly considered to be an effective pest management strategy for cocoa mirids, yet shade management recommendations are not based on extensive knowledge of the mirid ecology in traditional cocoa agroforests. 2 The main objectives of the present study were an assessment of the impact of shade on the spatial distribution of mirid populations and thus the evaluation of shade management strategies. 3 Mirid densities were measured and shade was characterized for three plots located in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 20 publications
7
72
0
4
Order By: Relevance
“…Beginning in July, developing fruits changed gradually to mature pods and the rate of damaged fruits increased and reached a peak in September (in 2004). This result can be explained by two factors: Þrst, this period coincides with a peak in the population of some true bug species, particularly the cocoa mirid S. singularis, the most common species on cocoa farms in Cameroon (Babin et al 2010). Second, during this period, cocoa fruits already are welldeveloped and their further development is not disturbed greatly by true bugs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Beginning in July, developing fruits changed gradually to mature pods and the rate of damaged fruits increased and reached a peak in September (in 2004). This result can be explained by two factors: Þrst, this period coincides with a peak in the population of some true bug species, particularly the cocoa mirid S. singularis, the most common species on cocoa farms in Cameroon (Babin et al 2010). Second, during this period, cocoa fruits already are welldeveloped and their further development is not disturbed greatly by true bugs.…”
Section: Discussionmentioning
confidence: 83%
“…Black pod disease caused by Phytophthora megakaria Brasier & M.J. GrifÞn (Pythiales: Pythiaceae) can induce losses of up to 80% of pods in some areas (Despré aux et al 1988). The cocoa mirid Sahlbergella singularis Haglund (Heteroptera: Miridae) is the most commonly found insect pest on Cameroonian cocoa farms (Babin et al 2010). This plant bug is particularly harmful because it damages fruits, twigs, and foliage, leading to a loss of productivity (25Ð 40% depending on the area), premature aging, and sometimes the rapid death of the most severely damaged trees (Williams 1953).…”
mentioning
confidence: 99%
“…Our results showed that environmental conditions influenced the way farmers managed their cocoa tree stands. In the forest-savannah transition zone of Bokito, the lower densities of tree species associated with cocoa trees fostered mirid outbreaks (Babin et al 2010) and Imperata cylindrica infestation. This led most farmers to spray their cocoa tree stands with insecticides and weed them more often than in the Zima and Ngomedzap forest zones.…”
Section: Discussionmentioning
confidence: 99%
“…In Cameroon, mirid bug populations of traditional cacao agroforestry systems are concentrated on cocoa trees that grow exposed to sunlight, in areas where there is a break in the canopy cover (Babin et al 2010). Thus, highly concentrated Sahlbergella singularis populations can be found in 'mirid pockets' that spread over 20-30 adjacent infested cocoa trees.…”
Section: Direct and Indirect Architectural/physical Effectsmentioning
confidence: 99%